Impact of interprofessional service-learning on the effectiveness of knowledge transfer of antimicrobial resistance to Hong Kong elders: a quasi-experiment - Anna C. Y. Lo; Joyce T. S. Li; Janita P. C. Chau; Samuel Y. S. Wong; David S. C. Hui; Vivian W. Y. Lee (Antimicrobial Resistance and Infection Control, 2021)
Abstract Background Community perception on antimicrobials plays a role in driving the development of antimicrobial resistance (AMR). The aim of the study was to evaluate the impact of interprofessional service-learning on the effectiveness of AMR knowledge transfer in Hong Kong elders aged 65 or above and students from university and secondary schools. Methods A quasi-experimental pretest–posttest controlled study was carried out from July 2018 to March 2019 for elderly subjects and a pre- and post-test were conducted in students from May to August 2018. Elderly subjects were recruited from the university-based community outreach program. The community outreach team consisted of both university and secondary school students. Students were provided with training of geriatric care and AMR before they reached out to the community. The one-to-one intervention with the aid of video and verbal explanation to educate the elderly about the definition, causes, and consequences of AMR, and preventive measures against AMR was provided. Questionnaires on knowledge of antibiotics and AMR were used as tools to reflect on the effectiveness for both students and elderly subjects. The questionnaire was completed twice, before and 1 week after the intervention. Chi-square test, t tests and regression analysis were used to analyze the data. Results A total of 93 Chinese elders, 61 of them in the intervention group and 32 in the control group participated in the study. The score obtained by the intervention group increased from 40.1 to 83.3% (p < 0.001) following intervention, while that of control group increased from 33.0 to 44.0% (p < 0.001). The increase attained in the intervention group was significantly greater than that of the control group (p < 0.001). A total of 95 secondary students and 88 university students have completed the pre-post questionnaires with 42.21% and 13% increment in AMR knowledge after the training (p < 0.001). Conclusion The significant change in knowledge level showed effective AMR knowledge transfer to both elders and students. The study could be used as a reference when allocating resources to implement effective interprofessional service-learning for better community health education in elderly populations. Trial registration: This study was approved by the Chinese University of Hong Kong Survey and Behavioural Research Ethics Committee in December 2018 (Ref no. SBRE-18-214).